The quality and safety of locum doctors: a narrative review. (November 2019) - Ferguson, Jane; Walshe, Kieran
Summary: Locum doctors are often perceived to present greater risks of causing harm to patients than permanent doctors. After eligibility and quality assessment, eight empirical and 34 non-empirical papers were included in a narrative synthesis to establish what was known about the quality and safety of locum medical practice. Empirical literature was limited and weak methodologically. Locums enabled healthcare organisations to maintain appropriate staffing levels and allowed staffing flexibility, but they also gave rise to concerns about continuity of care, patient safety, team function and cost. There was some evidence to suggest that the way locum doctors are recruited, employed and used by organisations, may result in a higher risk of harm to patients. A better understanding of the quality and safety of locum working is needed to improve the use of locum doctors and the quality and safety of patient care that they provide.